Adolescents’ Filial Piety Attitudes in Relation to Their Perceived Parenting Styles: An Urban–Rural Comparative Longitudinal Study in China - Li Lin; Li Lin; Qian Wang (Frontiers in Psychology, 2022)
The Dual Filial Piety Model (i.e., the model of reciprocal and authoritarian filial piety) offers a universally applicable framework for understanding essential aspects of intergenerational relations across diverse cultural contexts. The current research aimed to examine two important issues concerning this model that have lacked investigation: the roles of parental socialization (i.e., authoritative and authoritarian parenting styles) and social ecologies (i.e., urban vs. rural settings that differ in levels of economic development and modernization) in the development of reciprocal and authoritarian filial piety attitudes. To this end, a two-wave short-term longitudinal survey study was conducted among 850 early adolescents residing in urban (N = 314, 49.4% females, mean age = 13.31 years) and rural China (N = 536, 45.3% females, mean age = 13.72 years), who completed questionnaires twice, 6 months apart, in the spring semester of grade 7 and the fall semester of grade 8. Multigroup path analyses revealed bidirectional associations over time between perceived parenting styles and adolescents’ filial piety attitudes, with both similarities and differences in these associations between urban and rural China. In both settings, perceived authoritative parenting predicted increased reciprocal filial piety 6 months later, whereas perceived authoritarian parenting predicted reduced reciprocal filial piety among urban (but not rural) adolescents over time. Moreover, in both settings, reciprocal filial piety predicted higher levels of perceived authoritative parenting and lower levels of perceived authoritarian parenting 6 months later, with the latter effect being stronger among urban (vs. rural) adolescents. Adolescents’ perceived parenting styles did not predict their authoritarian filial piety over time; however, authoritarian filial piety predicted higher levels of perceived authoritative parenting (but not perceived authoritarian parenting) 6 months later in both settings. The findings highlight the roles of transactional socialization processes between parents and youth as well as social ecologies in the development of filial piety, thus advancing the understanding of how the universal human motivations underlying filial piety may function developmentally across different socioeconomic and sociocultural settings.